Effect of Shoulder Rehabilitation on Acromiohumeral Distance in Rotator Cuff-related Shoulder Pain: A Quasi-experimental Study - R Pruthviraj; KU Dhanesh Kumar; Stephiya Davis; Anusha V Shenai (Journal of Clinical and Diagnostic Research)
Introduction: Rotator Cuff-related Shoulder Pain (RCRSP) is a common musculoskeletal condition that causes pain and functional limitations. Reduced Acromion Humeral Distance (AHD) is associated with shoulder dysfunction in RCRSP. The Shoulder Symptom Modification Procedure (SSMP) may improve AHD and patient outcomes. Aim: To investigate the effectiveness of a 12-week SSMP on AHD in individuals with Rotator cuff-related shoulder pain. Materials and Methods: A single-blinded quasi-experimental study was conducted in the Department of Musculoskeletal Physiotherapy at RV College of Physiotherapy, Bengaluru, Karnataka, India, involving 60 participants aged 20 to 60 years with shoulder pain. Recruitment took place over six months, from February 2022 to July 2022. The researcher who performed the SSMP assessment and treatment was blinded to the pre- and post-test results of ultrasound imaging for AHD and Shoulder Pain and Disability index (SPaDi) scores. The response-guided treatment based on the SSMP assessment was administered twice a week for 12 weeks, with each session lasting 45 minutes. Pre-assessment of AHD and SPADI scores was conducted by an assessor, who also performed the follow-up evaluation after 12 weeks. Data were analysed using a paired t-test with R Software version 4.1.0, and a p-value <0.05 was considered statistically significant. Results: The mean age was 42.67±11.46 years. At baseline, the mean AHD was 8.54±1.11 mm, significantly increasing to 9.14±1.11 mm after 12 weeks. The pre-test mean SPADI score was 64.77±30.22, significantly reducing to 10.33±6.5 post-intervention. A paired t-test revealed a significant reduction in SPADI scores (t=19.33, p-value <0.0001). The pre-test AHD was 8.54±1.11 mm, and the post-test AHD significantly increased to 9.14±1.11 mm (t=4.19, p-value <0.0001). Conclusion: The 12-week SSMP significantly improved AHD and shoulder function in individuals with RCRSP. SSMP is an effective intervention for enhancing shoulder joint space, reducing pain, and minimising disability. Further studies are required to assess its long-term effects.